Laparoscopic hepatectomy is a safe procedure for cancer patients - Pilgrim, Charles H C (Blackwell Publishing Ltd, 2009)
BACKGROUND: Utilizing laparoscopy for major surgeries such as hepatectomy is a relatively new concept. Initially, benign pathologies dominated indications for resection. Our experience in an Australian setting with primarily malignant diagnoses is described. METHODS: A review of patients' profiles, pathology, surgery and outcome was performed on 35 patients between December 2005 and August 2008. Data were collected and analysed retrospectively from medical records on a pre-designed datasheet. RESULTS: Commonest indication for resection was colorectal metastasis (54%), 71% of all resections were for malignancy. Average operating time was 2 h 31 min (range 30 min–7 h, 15 min). Major morbidity consisted of one bile leak, two subphrenic abscesses and one pulmonary embolus. There were no deaths. Conversion to open was required in 20% and two patients required intra-operative blood transfusions. Average length of stay overall was 6.1 days (range 1–27), but as low as 2 days for some left lateral sectionectomies. Cessation of parenteral analgesia, return to normal diet and full mobility were achieved on average at 2.4, 2.3 and 2.8 days. Significant post-operative liver dysfunction was seen in two patients, which returned to normal by discharge. One patient died of disease progression 4 months after surgery. There were two involved margins in 35 patients (6%). CONCLUSIONS: Laparoscopic hepatectomy is a developing and safe technique in a select group of patients including those with malignancies, resulting in short hospital stays, rapid return to normal diet, full mobility and minimal morbidity with acceptable oncological parameters. This study is not comparative in nature, but provides evidence to support further investigation and establishment of this new technique for liver resection.